Mrs Esther Levy: Jewish Cookery Book - Davidson, Alan E (Petits Propos Culinaires, 2025)
Mrs Esther Levy: Jewish Cookery Book: W. S. Turner, Philadelphia, 1871, now reprinted in facsimile by the Pholiota Press, Post Office Box DB, Garden Grove, CA 92642: 200 pp. plus some 19th century advertisements, one illustration (of the synagogue which Mrs Levy ’may well have attended’), casebound 12.95, paperback 8.95.